IJPE 2018
DOI: 10.23940/ijpe.18.04.p6.639646
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Early Warning Method of Student Study Failure Risk based on Fuzzy Synthetic Evaluation

Abstract: As more and more students fail in course studies, higher education is now facing challenges regarding increasingly lower course completion rates as well as overall graduation rates. However, failures in course studies is a comprehensive result of various factors, which is characterized by uncertainty. To deal with this issue, fuzzy sets theory and fuzzy logic are advantageous compared with traditional methods. In this study, based on dynamic student study process data, a fuzzy synthetic evaluation method for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The other category is machine learning approaches. For example, decision tree and association rules [13], support vector machine [14], Bayesian algorithm [15], BP artificial neural network [16], genetic algorithm [17], and fuzzy comprehensive evaluation [18] were all applied in the prediction of students' learning performance and identification of at-risk students with learning difficulties. From these, it can be noted that research on learning performance prediction methods has shown a trend of algorithmization and automation.…”
Section: The Research On Prediction Algorithmsmentioning
confidence: 99%
“…The other category is machine learning approaches. For example, decision tree and association rules [13], support vector machine [14], Bayesian algorithm [15], BP artificial neural network [16], genetic algorithm [17], and fuzzy comprehensive evaluation [18] were all applied in the prediction of students' learning performance and identification of at-risk students with learning difficulties. From these, it can be noted that research on learning performance prediction methods has shown a trend of algorithmization and automation.…”
Section: The Research On Prediction Algorithmsmentioning
confidence: 99%